KANADA DAVLATIDA YOʻL QOPLAMALARI UCHUN ISHLATILADIGAN BETON TURLARI VA ULARNING AHAMIYATI (Multidisciplinary Journal of Science and Technology, 2025)
As a country characterized by harsh winter conditions, heavy traffic loads, and frequent freeze-thaw cycles, Canada relies on specialized types of concrete to sustainably build and maintain its road infrastructure. This article provides detailed information on the main types of concrete used in Canadian road pavements, their properties, and how they are adapted to national standards.